Performance Assessment of the Semajid River Watershed and Improvement Strategy Through Land Cover Optimization - Mohammad Afif Hasan; Entin Hidayah; Indra Nurtjahjaningtyas; Mokhammad Farid Ma’ruf (Journal of Applied Geospatial Information, 2026)
The Semajid River Basin (DAS) faces complex environmental problems, including flooding during the rainy season, drought during the dry season, increased river sedimentation, and uncontrolled land use changes. This study aims to assess the performance of the Semajid Watershed in accordance with the Minister of Forestry Regulation Number 61 of 2014 on Monitoring and Evaluation of Watershed Performance, and to formulate strategies to improve watershed performance through land-cover optimization scenarios. The watershed performance assessment includes criteria for land, water management, socio-economics, building investment value, and space utilization. The evaluation results show that the Semajid Watershed performance value is 113.75, which indicates that the watershed is in the category of needing to be saved. The application of the additional land cover scenario has a significant impact on improving the criteria for vegetation cover and protected areas. The Percentage of Permanent Vegetation Cover (PPV) increased from 5.5% (very high recovery category) to 32.44% (low recovery category), while the value of the protected area criteria decreased from 68.64 to 9.37, indicating an improvement in the ecological condition of the watershed. Although the watershed's carrying capacity increased to 107.5, the Semajid watershed remains in need of restoration. Therefore, restoration of the Semajid watershed requires integrated management that sustainably integrates technical and non-technical efforts.